DARE Newsletter, Vol. 4, No. 2, Spring 2001 - DARE; Frazer, Tim; Simon, David (Dictionary of American Regional English, 2001)
Contents: "Memories of DARE Communities" by Tim Frazer; "Funding Update" by David Simon; "DARE in the News and on the Podium"; "Coming in Volume IV"; "In Memoriam: Margaret Waterman"; "Staff Member Profile: Leonard Zwilling"; "Notes and Quotes"; "DARE Awarded NEH Grant"; "Ask a Fieldworker: August Rubrecht"; "Where Are They Now?: Lida Wagner"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Fieldwork; Lexicography; Regional English; English Language--Dialects--United States